Peran Desain Pekerjaan Dalam Meningkatkan Kualitas Hidup Kerja Karyawan - Nasution, Abdul Fattah; Diamsyah, Yuda Nur; Lubis, Erfiani; Lubis, Muhammad Ardiansyah Putra (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2024)
This study discusses the role of job design in improving employees' quality of work life. Job design plays an important role in improving employees' quality of work life. This study examines how elements of job design, such as tasks, responsibilities, and work environment, can affect employee satisfaction and productivity. This study shows that good job design can increase employee engagement, reduce stress, and create a more positive work atmosphere. By designing jobs that are in accordance with employee needs and expectations, companies can create a work environment that supports employee well-being and effectiveness. The results of this study are expected to provide insight for managers and organizational leaders in designing more effective job design strategies. Job design plays an important role in improving employees' quality of work life (QWL), which has an impact on their satisfaction and performance. Research shows that good job design can reduce turnover and absenteeism, and increase organizational commitment. QWL includes elements such as autonomy, task variety, and a conducive work environment. By paying attention to job design, companies can create a better work atmosphere, so that employees feel motivated and motivated to contribute more optimally.